1989
DOI: 10.1037/0033-2909.106.2.231
|View full text |Cite
|
Sign up to set email alerts
|

Theory and research concerning social comparisons of personal attributes.

Abstract: Social comparison theory has evolved considerably since Festinger (1954) originally proposed it. This article integrates these changes with insights offered by recent social comparison studies and by research on social cognition and the self. Contrary to the original theory or subsequent research, (a) the individual is not always an unbiased self-evaluator but may seek many goals through social comparison; (b) the social environment may not be inactive but may impose unwanted comparisons; and (c) the compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
1,326
3
34

Year Published

1996
1996
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,609 publications
(1,410 citation statements)
references
References 128 publications
(265 reference statements)
47
1,326
3
34
Order By: Relevance
“…Some patients on the other hand, felt that group exercise was inhibiting. This effect is also found in bladder patients 35 and in chronic low back patients who expressed feelings of embarrassment when training in a group. 36 For these patients, telerehabilitation treatment would address their desire to exercise privately.…”
Section: Discussionmentioning
confidence: 59%
“…Some patients on the other hand, felt that group exercise was inhibiting. This effect is also found in bladder patients 35 and in chronic low back patients who expressed feelings of embarrassment when training in a group. 36 For these patients, telerehabilitation treatment would address their desire to exercise privately.…”
Section: Discussionmentioning
confidence: 59%
“…Based on social comparison theory [40], research has shown that students' selfconcepts are highly influenced by their social environment and the social comparisons provided by this environment [41]. Langford et al [42] point out, for example, that perceived social support leads to more accurate perceptions of normative peers [43].…”
Section: Characteristics Of Instructional Quality Mathematics Self-comentioning
confidence: 99%
“…They try to distance themselves from failure and associate themselves with success by attributing the former to external factors, but claim (sometimes unwarranted) personal responsibility for the latter (e.g., Schlenker, Weigold, & Hallam, 1990;Dauenheimer, Stahlberg, Frey & Petersen, 2002). They also tend to protect self-esteem via favorable social comparisons or ingroup identification (e.g., Turner, Hogg, Turner, & Smith, 1984;Wood, 1989).…”
Section: How Success and Failure Affects Self-evaluation And Self-esteemmentioning
confidence: 99%